Fast charge-carrier trapping in TiO2 nanotubes - Wehrenfennig, C; Palumbiny, C; Snaith, H; Johnston, M; Schmidt-Mende, L; Herz, L (American Chemical Society, 2015)
One-dimensional semiconductors such as nanowires and nanotubes are attractive materials for incorporation in photovoltaic devices as they potentially offer short percolation pathways to charge-collecting contacts. We report the observation of free-electron lifetimes in TiO2 nanotubes of the order of tens of picoseconds. These lifetimes are surprisingly short compared to those determined in films of TiO2 nanoparticles. Samples of ordered nanotube arrays with several different tube wall thicknesses were fabricated by anodization and have been investigated by means of optical-pump-terahertz-probe (OPTP) spectroscopy, which allows measurement of transient photoinduced conductivity with picosecond resolution. Our results indicate a two-stage decay of the photoexcited electron population. We attribute the faster component to temporary immobilization of charge in shallow trap states, from which electrons can detrap again by thermal excitation. The slower component most likely reflects irreversible trapping in states deeper below the conduction band edge. Free-electron lifetimes associated with shallow trapping appear to be independent of the tube wall thickness and have very similar values for electrons directly photoexcited in the material and for those injected from an attached photoexcited dye. These results suggest that trap states are not predominantly located at the surface of the tubes. The effective THz charge-carrier mobility in the TiO2 nanotubes is determined (0.1-0.4 cm2/(Vs)) and found to be within the same range as carrier mobilities reported for TiO2 nanoparticles. Implications for the relative performance of these nanostructures in dye-sensitized solar cells are discussed.